The Effect of Dream Anxiety on Sleep Quality in Inflammatory Bowel Diseases - SAKALLI KANİ, AYŞE; KAHRAMAN, MERVE MERİÇ; ATUĞ, ÖZLEN (KARGER, 2020)
Introduction:Declining sleep quality is a well-known issue in inflammatory bowel disease (IBD), but dream characteristics of patients with IBD and their role in sleep quality are unknown. In this study, we aimed to examine whether and how patients with ulcerative colitis (UC) and Crohn's disease (CD) differ on sleep quality, sleepiness level, and dream anxiety (DA) level compared to healthy controls (HC), controlling for their depressive and anxious tendencies.Methods:Patients and HCs were enrolled prospectively into the study. The Van DA Scale, Pittsburg Sleep Quality Index, Epworth Sleepiness Scale, Beck Depression Index, and State-Trait Anxiety Inventories were used to assess DA, sleep quality, sleepiness, depression, and anxiety, respectively.Results:Patients with IBD had significantly lower depression (p= 0.004), state anxiety (p= 0.0001), trait anxiety (p= 0.004), and DA (p= 0.0001) than HCs. Although no statistically significant difference in sleep quality was found (p= 0.99), daytime sleepiness was more common in HCs than in IBD patients (p = 0.0001). No statistically significant difference was seen in depression, state anxiety, trait anxiety, DA, sleep quality, and daytime sleepiness between patients with CD and those with UC. No correlation was found between disease activity indices and psychological parameters.Conclusion:In contrast to previous studies, this study found lower anxiety and depression levels in patients with IBD than in HCs. Moreover, DA score was higher in HCs. For the first time, we revealed that DA may be one of the factors leading to sleep disturbance in patients with IBD.
Keywords: Ulcerative colitis; Inflammatory bowel disease; Anxiety; Crohn's disease; Depression; Dream anxiety; ULCERATIVE-COLITIS; FAMILY CAREGIVERS; NIGHTMARES; DISORDERS; THERAPY; INDEX; DISTURBANCES; COMORBIDITY; DEPRESSION; SYMPTOMS